Seven Rules for Social Research - Firebaugh, Glenn (Book collections on Project MUSE., 2008)
'Seven Rules for Social Research' teaches social scientists how to get the most out of their technical skills and tools, providing a resource that fully describes the strategies and concepts no researcher or student of human behaviour can do without.